2021
DOI: 10.1021/acs.jpcb.1c07699
|View full text |Cite
|
Sign up to set email alerts
|

Correlation in Domain Fluctuations Navigates Target Search of a Viral Peptide along RNA

Abstract: Biological macromolecules often exhibit correlations in fluctuations involving distinct domains. This study decodes their functional implications in RNA–protein recognition and target-specific binding. The target search of a peptide along RNA in a viral TAR–Tat complex is closely monitored using atomistic simulations, steered molecular dynamics simulations, free energy calculations, and a machine-learning-based clustering technique. An anticorrelated domain fluctuation is identified between the tetraloop and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…We have investigated various systems ranging from simple duplex (BIV TAR RNA), triplex (BWYV RNA PK) to numerous complex folded RNA structures (flavivirus sfRNA, SARS-CoV-2 RNA PK, SAM-I riboswitch aptamer, to name a few). 12,19,51,73,139 In all these systems we have primarily observed three distinguishable modes of interaction, representing their characteristic peaks in the RDF plot as shown in Fig. 1A.…”
Section: Discussionmentioning
confidence: 87%
“…We have investigated various systems ranging from simple duplex (BIV TAR RNA), triplex (BWYV RNA PK) to numerous complex folded RNA structures (flavivirus sfRNA, SARS-CoV-2 RNA PK, SAM-I riboswitch aptamer, to name a few). 12,19,51,73,139 In all these systems we have primarily observed three distinguishable modes of interaction, representing their characteristic peaks in the RDF plot as shown in Fig. 1A.…”
Section: Discussionmentioning
confidence: 87%
“…Like any other study, computational studies are aimed at understanding the mechanism of viral infection as it relates to the development of new small-molecule drugs that inhibit virus-host cell binding. A wide range of approaches are actively involved in non-empirical studies of viruses-from a bioinformatics analysis (see, for instance, [4,5]) to coarse-grained computational modeling [6] and long-timescale allatom MD simulations (see, for instance, [7][8][9][10]) as well as a fashionable machine-learningbased clustering technique [11] including deep learning [12,13]. A detailed review of various computational methods and their combinations can be found in [3], where such aspects as molecular biophysics, bioinformatics, cheminformatics, machine learning, and mathematics are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, using atomistic simulations, recently, we identified intricate allosteric cross-talk between the distant bulge and loop in BIV TAR RNA. 30 There, we have shown how the hierarchical fluctuations of the loop and bulge guide a protein to find the target binding site along RNA.…”
mentioning
confidence: 99%